2020
DOI: 10.1109/access.2020.2965619
|View full text |Cite
|
Sign up to set email alerts
|

Process-Oriented Quality in e-Learning: A Proposal for a Global Model

Abstract: Nowadays, all the universities that offer courses in the e-learning modality seek to improve and differentiate more and more from their competitors. One possible way forward is without doubt to implement standards and good practices. These allow us to guarantee the quality in the implementation or maintenance of the entire e-learning system. The problem is the diversity of existing standards and good practices because they can generate confusion in the selection of the most appropriate. The ideal would be to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…In this case, the student is an active recipient in this process, since the student structures the pedagogical act, trying to develop what is established in the didactic guide (Rajabalee & Santally, 2020), the contents are not purely theoretical; they are usually interactive; in addition, students can access other resources available on the network (Ben, Abid & Meddeb, 2020). Comparing e-learning and distance learning, it can be observed that there is a change of direction and perspective; in this case, the pedagogical perspective changes substantially (Vagarinho & Llamas-Nistal, 2020) for the learner.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the student is an active recipient in this process, since the student structures the pedagogical act, trying to develop what is established in the didactic guide (Rajabalee & Santally, 2020), the contents are not purely theoretical; they are usually interactive; in addition, students can access other resources available on the network (Ben, Abid & Meddeb, 2020). Comparing e-learning and distance learning, it can be observed that there is a change of direction and perspective; in this case, the pedagogical perspective changes substantially (Vagarinho & Llamas-Nistal, 2020) for the learner.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent research by Wang et al [13] has emphasized the collaborative learning model using Internet-of-Things (IoT). The work carried out by Vagarinho et al [14] has discussed process-oriented learning to improvise the teaching quality focusing on the e-learning system. A similar direction has also been carried out by Pham et al [15], where a smart education system using digital transformation is emphasized.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some barriers to make an effective implementation of the e-learning system. In some of the positives that save time and effort, low costs, easy return to the scientific topic, and for the negatives, there are many who face difficulties in accessing the educational platform and other technical problems [3].…”
Section: Introductionmentioning
confidence: 99%
“…It will make it easier and flexible for the students [9]. Vagarinho, Llamas-Nistal (2019) suggests universities that providing e-learning system should have a competitive advantage to attract students to them [3]. This can by enhancing the rules and policies that are implemented by these universities.…”
Section: Introductionmentioning
confidence: 99%